Screen-Time Dan Konsumsi Kopi Dengan Status Gizi Dan Lama Tidur Pada Orang Dewasa (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2023)
Excess and malnutrition in adulthood are serious problems that increase the risk of disease. Nutritional status can be influenced by several factors, one of which is coffee consumption and screen time. Coffee consumption and screen-time can be impactful to a person's length of sleep. The purpose of this study was to clarify the relationship between screen time and coffee consumption with length of sleep and nutritional status in the population aged 20 to 45 years who lived in Buttu Sawe Village, Pinrang District. This type of research is observational research with a cross-sectional research approach. The sample is the entire adult community aged 20-45 years in Buttu Village, Pinrang Regency. The sampling technique was carried out using the purpossive sampling method of 100 people. Bivariate analysis using pearson correlation test. The results showed that there was no relationship between coffee consumption (r = 0.150, p = 0.136) and nutritional status (r = -0.087, p = 0.388), there was no relationship of screen-time with sleep length (r = -0.020, p = 0.847) and there was a screen-time relationship with nutritional status (r = -0.434, p = 0.000).